HARMONISASI PRINSIP-PRINSIP TRIPS AGREEMENT DALAM HAK KEKAYAAN INTELEKTUAL DENGAN KEPENTINGAN NASIONAL - tri setiady (Universitas Lampung, 2014)
The research aims to find a legal politics of harmonization the Intellectual Property Rights (IPR) of Indonesia with WTO/TRIPs agreement. Based on the juridical approach of secondary data, it was concluded that there is a harmonization between legal arrangements of IPR with the WTO/TRIPs agreement. The reason given by the government is because Indonesia has ratified the WTO/TRIPs agreement, and it is 'full complience' and 'non-reservation', and due to the insistence of developed countries of IPR owners against Indonesia and the needs of national IPRs. There is no courage to create legal politics of our own IPR, which is derived from the philosophy of Pancasila, 1945 Constitution and national interests. Fear of the threat of developed countries must be resisted and overcome by intelligence. Keywords: Trips Agreement, Intellectual Property Rights , National Interest